(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper introduces two classes of continuous functions defined between an ideal topological space and a bitopological space, called almost quasi τ^(σ_1,σ_2)-continuous functions and weakly quasi τ^(σ_1,σ_2)-continuous functions. Furthermore, several characterizations and some properties concerning almost quasi τ^(σ_1,σ_2)-continuous functions and weakly quasi τ^(σ_1,σ_2)-continuous functions are investigated. Moreover, the relationships between almost quasi τ^(σ_1,σ_2)-continuity and weak quasi τ^(σ_1,σ_2)-continuity are considered.